Diet-gut microbial interactions influence cancer immunotherapy - Wang, Xue; Geng, Shitao (Frontiers in Oncology, 2023)
The gut microbiome is involved in the absorption and metabolism of host nutrients and modulates the immune response, affecting the efficacy of immunotherapy for cancer. In patients receiving immunotherapy, appropriate modifications of gut microbiota are thought to improve therapeutic response. Of all the factors that influence the gut microbiota, diet is the most influential and modifiable. Healthy dietary patterns as well as some specific dietary components can help the growth of beneficial microbiota in the gut, thereby protecting against cancers and promoting human health. A growing number of researches have confirmed the positive effects of a diet-gut microbiota approach as an adjuvant therapy for cancer, but controversy remains. Here, we summarize the interactions between diet and gut microbes based on previous studies, and discuss the role of gut microbiota-based dietary strategies in tumor immunotherapy, with the potential mechanisms of actions also intensively discussed